2018
DOI: 10.1111/tpj.14071
|View full text |Cite
|
Sign up to set email alerts
|

Shedding light on the methylerythritol phosphate (MEP)‐pathway: long hypocotyl 5 (HY5)/phytochrome‐interacting factors (PIFs) transcription factors modulating key limiting steps

Abstract: The plastidial methylerythritol phosphate (MEP) pathway is an essential route for plants as the source of precursors for all plastidial isoprenoids, many of which are of medical and biotechnological importance. The MEP pathway is highly sensitive to environmental cues as many of these compounds are linked to photosynthesis and growth and light is one of the main regulatory factors. However, the mechanisms coordinating the MEP pathway with light cues are not fully understood. Here we demonstrate that by a diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 73 publications
1
30
0
Order By: Relevance
“…After the yeast one-hybrid experiment, we also see the confirmed result that GBF1 only bind to the segment 3 of DXSpro_WT region (containing G-box site). Interestingly, at the same time, it has been recently reported that PIFs regulated the DXS1 gene in Arabidopsis , probably through the PBE box (CACATG), whereas HY5 induces the expression of this gene through direct binding to the G-box containing core GCE element (ACGT) [34]. Importantly, we also provided evidence that overexpressing GBF1 in transgenic Poa pratensis plant elevate the transcript level of PpDXS1 gene.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…After the yeast one-hybrid experiment, we also see the confirmed result that GBF1 only bind to the segment 3 of DXSpro_WT region (containing G-box site). Interestingly, at the same time, it has been recently reported that PIFs regulated the DXS1 gene in Arabidopsis , probably through the PBE box (CACATG), whereas HY5 induces the expression of this gene through direct binding to the G-box containing core GCE element (ACGT) [34]. Importantly, we also provided evidence that overexpressing GBF1 in transgenic Poa pratensis plant elevate the transcript level of PpDXS1 gene.…”
Section: Discussionsupporting
confidence: 68%
“…Generally, GBFs can be divided into three sub-groups involved in the two TFs superfamily, basic region-leucine zipper (bZIP) and basic helix-loop-helix (bHLH) types [33]. Long hypocothyl 5 (HY5) protein and phytochrome interacting factors (PIFs) are typical representatives of the two sub-groups of GBFs respectively [34]. Besides, proline-rich domain of GBF-1 protein (bZIP type) contribute to the function of activating transcription in Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…The significant accumulation of cis ‐carotenoids observed in the clb5 mutant grown under low light is counterintuitive to what is known about the regulation of the carotenogenic genes under low light (Llorente et al ., 2017). The rate‐limiting PSY enzyme is enhanced by light at the transcriptional, translational, and post‐translational levels (von Lintig et al ., 1997; Nisar et al ., 2015; Chenge‐Espinosa et al ., 2018). However, this result is consistent with the idea that under low light fluences the degradation or non‐enzymatic modification of these carotenoids, in particular ζ‐carotene, decreases.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, ceh1 seedlings grown in Rc accumulated high MEcPP levels, a phenotype that was partially (∼10-fold) suppressed in ceh1/phyB-9 seedlings. This reduction was not unexpected since phyB controlled PIF regulates the expression of DXS , the first MEP-pathway gene encoding the flux determinant enzyme (Chenge-Espinosa et al, 2018). It is noteworthy that despite this significant reduction, the MEcPP content of ceh1/phyB-9 seedlings remained ∼100-fold above those of WT or phyB-9 plants grown simultaneously and under the same conditions.…”
Section: Resultsmentioning
confidence: 95%